MuSyC is a consensus framework that unifies multi-drug synergy metrics for combinatorial drug discovery - David J. Wooten (Nature Portfolio, 2021)
The lack of a unifying metric characterizing combinatorial drug interactions has impeded the development of combinatorial therapies. Here, the authors present MuSyC, a consensus synergy metric that overcomes several caveats associated with other, popular metrics.